On Optimal Management of Financial Pyramid - Artem V. LOGACHOV; Sergey Ye. KHRUSHCHEV; Vladimir V. GLINSKIY; Mikhail A. ALEKSEEV; Lyudmila K. SERGA; Marina V. PUDOVA (Communications of International Proceedings, 2021)
The paper considers the model of financial pyramid, where, contrary to the formations studied earlier, it is assumed that an organizer invests the funds received from the participants into risk-free assets at some interest which is accrued continuously. The optimization problem of maximization of proceeds at the moment of the end (crash) of the financial pyramid is solved within the specified assumptions. The obtained solution has an analytic form.
Keywords: Model of financial pyramid; Crash of financial pyramid; Maximization of proceeds of financial pyramid